The manufactured crisis myths, fraud, and the attack on America's public schools - Berliner, David C. 1938-; Biddle, Bruce J. 1928- (Addison-Wesley, 1995)
In The Manufactured Crisis, two prominent scholars, prize-winning educational psychologist David C. Berliner and leading social psychologist Bruce J. Biddle, fight back with the good news. They debunk a whole series of familiar but untrue statistics about public schools - that SAT scores have been dropping, when for many groups they are in fact rising; that illiteracy is up, when in fact the numbers have been skewed because schools are now educating the traditionally disenfranchised in ever larger numbers; that investments in public education do not pay off when, in fact, they lead to greater student achievements and life earnings; that private schools are inherently better than public schools when, in fact, the evidence does not support this charge